Project-Based Learning Innovation in Islamic Education: Enhancing Students’ Spiritual Competence at MTs Muhammadiyah Bima - Supriadin Supriadin; Lukman Lukman (Ar-Fachruddin: Pendidikan Agama Islam, 2025)
Research Objective– This study aims to examine how Project-Based Learning (PjBL) functions as an instructional innovation in Islamic education to enhance students’ spiritual competence at MTs Muhammadiyah Bima. The research focuses on understanding the pedagogical processes, learning experiences, and spiritual outcomes generated through the implementation of PjBL in Islamic education classrooms. Methodology– Employing a qualitative case study design, the research involved Islamic education teachers, students of grades VIII–IX, and school administrators at MTs Muhammadiyah Bima. Data were collected through semi-structured interviews, classroom observations, and document analysis, enabling an in-depth exploration of teaching practices and student learning experiences. The data were analyzed using thematic analysis, supported by triangulation of sources and methods to ensure credibility, dependability, and trustworthiness of the findings. Findings– The findings reveal that PjBL significantly enhances students’ spiritual competence through the deeper internalization of Islamic values, collaborative spiritual practices, reflective and critical thinking, and the observable integration of religious values into daily behavior. Students demonstrated increased moral awareness, ethical reasoning, responsibility, social empathy, and active engagement in faith-based practices both inside and outside the classroom. Research Implications/Limitations–  The study highlights PjBL as an effective model for holistic Islamic education but is limited to a single institutional context, restricting broader generalization. Originality/Value– his research contributes original insights by foregrounding spiritual competence as a core outcome of PjBL within the Muhammadiyah madrasah context, enriching discourse on innovative Islamic education pedagogy.